The Effectiveness of the Traditional Game Oray Orayan in Increasing the Associative Social Interaction of Elementary School Students - Marhamah, Yulis; Anisah, Ani Siti; Akmal, Rudi (Al-Aulad: Journal of Islamic Primary Education, 2024)
The purpose of this study was to determine the effectiveness of traditional oray-orayan games in improving the associative social interaction of elementary school students. This research is a quantitative research with pre-experimental design using One Group Pretest-Posttest design. The research sample of class IV SDN 3 Haruman, Garut Regency totalled 31 students. Data collection techniques were carried out with attitude scales and observations that had previously been judged by expert judgment. Attitude scale pretest posttest data were analysed using Normality test analysis, Homogeneity test, and continued with the sample t test, obtained results with a significance level of 0.05 for the attitude scale t count -6.26 and t table 2.0003 which means t count < t table Ha is accepted. For the attitude scale, the N-Gain test produced data of 0.50, which is "quite effective" within the range of 0.30 â‰¤ g < 0.70. The results of observations in the field show the category "good". It can be concluded that the traditional game of oray-orayan is proven effective in improving the associative social interaction of elementary school students.